Anthocyanin-enriched bilberry extract attenuates glycaemic response in overweight volunteers without changes in insulin. (January 2020) - Alnajjar, Mahasin; Kumar Barik, Sisir; Bestwick, Charles; Campbell, Fiona; Cruickshank, Morven; Farquharson, Freda; Holtrop, Grietje; Horgan, Graham; Louis, Petra; Moar, Kim-Marie; Russell, Wendy R; Scobbie, Lorraine; et al.
Graphical abstract: Highlights: This study investigated the effect of a three week supplementation of concentrated bilberry extract on glucose metabolism to determine what the initial mechanisms are causing the improvement in glucose homeostasis. This study demonstrates that the ingestion of a concentrated bilberry extract over a three week intervention period reduces postprandial glycaemia without changes in insulin. We show that the mechanism for the early decreased glycaemic response involves reduced rates of carbohydrate digestion/absorption. There was no change in anti-inflammatory markers (hsCRP, MCP-1, leptin), markers of vascular health (Apo A1, sVCAM-1, sICAM-1) in the plasma, reducing potential and radical scavenging capacity (as assayed through use of electron transfer [ET] and ET/hydrogen atom transfer based assays FRAP and TEAC respectively (Huang, Ou, & Prior, 2005; Apak et al., 2016) in plasma or change in the faecal bacterial microbiota measured between the volunteers receiving the bilberry extract and the placebo. Abstract: This study investigated the effect of a three week supplementation of bilberry extract on glucose metabolism. Overweight volunteers (n = 16; BMI 31) were given three capsules of either 0.47 g bilberry extract (36% (w/w) anthocyanins) or placebo per day for three weeks in a double blinded cross over intervention. The ingestion of the bilberry extract decreased the OGTT AUCi for glucose (20%; p = 0.008) but not for insulin compared with the placebo. There was no change in anti-inflammatory markers (hsCRP, MCP-1, leptin), vascular health markers (Apo A1, sVCAM-1, sICAM-1), reducing potential/ radical scavenging capacity or faecal bacterial microbiota. In vitro studies showed that the bilberry extract decreased α-amylase activity (p < 0.0001), α-glucosidase activity (p < 0.0001) and glucose uptake (p < 0.0001). This study demonstrates that the ingestion of a bilberry extract over a three week intervention period reduces postprandial glycaemia without changes in insulin. This is probably due to reduced rates of carbohydrate digestion and/or absorption.